Covariance for electromagnetic current for two bosons at higher order in the light front - Sales, J. H.; Suzuki, A. T. [UNESP]; Soriano, L. A. [UNESP] (AIP Publishing, 2010)
We show that the electromagnetic current for a system composed by two charged bosons has a structure of many bodies even in the impulse approximation, when described in the time x +. In terms of the two body component for the bound state, the current contains two body operators. We discuss the process of pair creation by the photon and interpret it as a zero mode contribution to the current and its consequences for the components of currents in the light front. © 2010 American Institute of Physics.
Keywords: Covariance; electromagnetic current; higher order; two bosons, light front